Mediamorphosis the dynamics of communication and socio-cultural change - Pusta, Maria Gwenetha Ybanez (Mutya Pubishing House, Inc., 2014)
"It tackles the role of mas media as an agent oof change and as a catalyst of development, in the light of contemporary communication, critical and cultural theories."--Preface